PEMANFAATAN LIMBAH ORGANIK SEBAGAI ENERGI ALTERNATIF MENGGUNAKAN REAKTOR GASIFIKASI DOWNDRAFT - Hasan Harun, Ervan; Ilham, Jumiati; Djafar, Romi; Djamalu, Yunita (Program Vokasi-Universitas Negeri Gorontalo, 2024)
Organic waste from coconut shells, corn cobs, candlenut shells, and lamtoro wood is often found in the Gorontalo region. The gasification of organic waste has the potential to reduce organic waste and produce gas for various applications, including heating, power generation, and industrial raw materials. The research aims to determine the gas composition of the downdraft gasification process from organic waste from coconut shells, candlenut shells, corn cobs, and lamtoro wood, to determine the rate of fuel consumption, and to determine the calorific value. The method used is an experimental method. Test results using a downdraft gasifier reactor with 5 kg of fuel. The average H2 value obtained from the test results for coconut shells was 12.46%, candlenut shells 13.01%, corn cobs 9.3%, and lamtoro wood 15.95%, the highest H2 value from several of these samples was obtained from lamtoro wood with the highest percentage was 15.95%, the average O2 value obtained was coconut shell 8.86%, candlenut shell 6.37%, corn cob 2.61%, lamtoro wood 5.22%, the average CH4 value was shell coconut 7.88%, candlenut shell 4.05%, corn cob 8.03%, lamtoro wood 7.32%, average CO value for coconut shell 0.56%, candlenut shell 0.05%, corn cob 10 .71%, lamtoro wood 0.05% while the average N2 value obtained was 70.21% coconut shell, 76.49% candlenut shell, 69.25% corn cob, and 71.44% lamtoro wood. The findings compare four organic wastes as alternative energy using a downdraft gasification reactor. The conclusion from this research is that the best gas composition is from corncob organic waste with H₂, CH₄, and CO of 28.05%, the longest burning rate on corncob samples is 23.11 grams/minute and the highest calorific value test is on lamtoro wood samples with results reaching 4,340 cal/gram.